Experiência estética e formação humana na perspectiva educativa de John Dewey - Morigi, Aline Franciele (2015)
This study deals with relationship between aesthetic experience and human formation from the John Dewey approach. The conception of aesthetic experience of this author allows to understand the experiences of the subjects in a context still marked by dualisms, in the perspective of an enrichment of such experiences and therefore under a formative perspective. The research problem is guided by the following question: what is the reach of the development of the aesthetic experience for the human formation from the monistic perspective of Dewey? Our hypothesis is that the monistic conception of experience from Dewey allows to think the aesthetic experience and the human education in a formative perspective. This dissertation is a theoretical and bibliographic research and adopts a hermeneutic methodological approach as bibliographic work procedure. The first chapter deals with Dewey’s conception of experience. The second chapter deals with Dewey's criticism to the dualisms as well as the aesthetic monism advocated by the author. Finally, the third chapter articulates the relationship between aesthetic experience and education as human formation in a monistic perspective.